Ovitrap use in epidemiology study of Aedes aegypti and Aedes albopictus in Kuta Alam sub-district Banda Aceh, Indonesia - Athaillah Farida; Abu Hasan Ahmad; Upik K. Hadi; Muhammad Hambal; Yudha Fahrimal; Rimaya Shafitri (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
A study on the mosquitoes Aedes spp. has been conducted in Kuta Alam Sub-district, Banda Aceh, to find out the percentage and distribution of positive ovitrap with eggs of Aedes aegypti and A. albopictus, based on location of ovitrap, level of rainfall as well as different landuse of settlement areas. Sampling was conducted by setting up ovitrap monthly, from January to December 2010 in settlement area that have more trees versus less trees, both indoor and outdoor. Data of the ovitrap percentage that was proved to be positive with eggs of A. aegypti and A. albopictus was analized using Student T-Test. The study revealed that rainfall value did not significantly affect (P0.05) the percentage of positive A. aegypti and  A. albopictus ovitraps and neither  did the location of ovitrap (indoor versus outdoor). The settlement areas with more trees have significantly higher percentage of ovitraps containing A. albopictus than areas with less trees, but not significant for A. aegypti (P0.05). It was suggested that rainfall and location of ovitrap did not influence the number of ovitrap containing Aedes aegypti and Aedes albopictus eggs, while settlement landuse  influenced significantly the percentage of positive ovitraps for Aedes albopictus, but not for Aedes. aegypti. Between two villages in Kuta Alam sub-district, it was found out that Gampong Beurawe was dominated by Aedes albopictus while Gampong Kuta Alam by Aedes aegypti. Overall, the sensitivity of ovitrap in Kuta Alam subdistrict was 83,7%. The usage of ovitrap is thus recommended for monitoring of Aedes spp. control programs